Does the golden lion tamarin, Leontopithecus rosalia (Primates: Callitrichidae), select a location whithin the forest strata for long distance communication? - Vera Sabatini; Carlos R. Ruiz-Miranda (Zoologia (Curitiba), 2010)
The effectiveness of auditory signals for long distance communication depends on environmental, biological and behavioral factors. Because the environment is not homogenous, it is expected that vocalizing animals would emit signals from locations (perches) that would facilitate call propagation and perception. Perching behavior has been widely documented in birds, but not in primates. The aim of this study was to ascertain whether golden lion tamarins - Leontopithecus rosalia (Linnaeus, 1766) - emit long calls from places (perch) within the forest strata that are higher above the ground with respect to places used for baseline behaviors. We compared the forest stratum (upper, middle and lower strata) and habitat type (hill, swamp and lowland forests) used for long calls with those used for other behaviors. The focal animal technique (n = 4) of 10 minutes with instantaneous sampling at two minutes were used if the subjects were not emitting long calls, and the all-occurrences technique if a focal individual emitted a two-phrase long call. Golden lion tamarins used all strata in all habitat types, including the ground, when they were not emitting long calls, but vocalized long calls most often from the upper strata, just underneath the canopy, in the three habitats studied. From a total of 29 bouts of long calls, 21 were initiated by individuals that were in the lower stratum; however, these individuals subsequently migrated to the upper stratum, while still vocalizing. Calling from the upper strata of the forest, just underneath canopy could improve sound transmission, perception, visual contact or a combination of these types of communication. Based on these considerations, we hypothetize that by placing themselves in the upper strata of the forest when emitting calls, golden lion tamarins enhance their likelhood to locate other callers, not only be improving sound reception, but also by increasing their chances to make visual contact with them.